(untitled) (GIST – Education and Learning Research Journal, 2020)
This article reports a case study conducted with twelve students from the Modern/Foreign Languages program at a public university in Colombia. It sought to unveil EFL Student’s perceptions on Gender Stereotypes through three different moments. At first, students expressed their thoughts after being exposed to a film. Then, their point of views were heard through the exposure of some before/now photographs; and lastly, they provided their insights through their own artwork. Data was gathered through focus group interviews, field notes and students’ artifacts. Findings showed that students’ perceptions on gender stereotypes differ from their past generations and the way they see their future have made their minds change over the time.